VAPYRIN Marks an Endosomal Trafficking Compartment Involved in Arbuscular Mycorrhizal Symbiosis - Bapaume, Laure; Laukamm, Sabine; Darbon, Geoffrey; Monney, Corinne; Meyenhofer, Felix; Feddermann, Nadja; Chen, Min; Reinhardt, Didier (Frontiers in Plant Science, 2019)
Arbuscular mycorrhiza (AM) is a symbiosis between plants and AM fungi that requires the intracellular accommodation of the fungal partner in the host. For reciprocal nutrient exchange, AM fungi form intracellular arbuscules that are surrounded by the peri-arbuscular membrane. This membrane, together with the fungal plasma membrane, and the space in between, constitute the symbiotic interface, over which nutrients are exchanged. Intracellular establishment of AM fungi requires the VAPYRIN protein which is induced in colonized cells, and which localizes to numerous small mobile structures of unknown identity (Vapyrin-bodies). In order to characterize the identity and function of the Vapyrin-bodies we pursued a dual strategy. First, we co-expressed fluorescently tagged VAPYRIN with a range of subcellular marker proteins, and secondly, we employed biochemical tools to identify interacting partner proteins of VAPYRIN. As an important tool for the quantitative analysis of confocal microscopic data sets from co-expression of fluorescent proteins, we developed a semi-automated image analysis pipeline that allows for precise spatio-temporal quantification of protein co-localization and of the dynamics of organelle association from movies. Taken together, these experiments revealed that Vapyrin-bodies have an endosomal identity with trans-Golgi features, and that VAPYRIN interacts with a symbiotic R-SNARE of the VAMP721 family, that localizes to the same compartment.